Human Dignity Conference - Part 2
Continuation of the international conference "On Human Dignity" in honor of outgoing Hungarian President Árpád Göncz held at the Hungarian Academy of Sciences in Budapest. The conference was organized by the Hungarian Academy of Sciences, Central European University and the Faculty of Law and Political Science of Eötvös Loránd University. The recording starts with Prof. János Kornai’s speech. It continues with Prof. Avishai Margalit (Professor at the Institute for Advanced Study in Princeton), Aryeh Neier (President of the Open Society Institute), Prof. Thomas Scanlon and Arch-abbot Asztrik Várszegi of Pannonhalma. Last to deliver a speech on human dignity is Cornelio Sommaruga (lawyer, diplomat and former President of the International Committee of the Red Cross). President Árpád Göncz closes the conference. This recording contains the moderator’s introductory words about the guests of the conference as well as the Q&A sessions.